A Fe3O4@SiO2/Schiff Base/Pd Complex as an Efficient Heterogeneous and Recyclable Nanocatalyst for One‐Pot Domino Synthesis of Carbamates and Unsymmetrical Ureas. Issue 37 (12th September 2019) - Inaloo, Iman Dindarloo; Majnooni, Sahar
Abstract : A palladium‐catalyzed domino method for the direct synthesis of carbamates and ureas has been developed by using readily available and economical starting materials (aryl halide, carbon monoxide, sodium azide, amines and alcohols) in a one‐pot approach. The domino process underwent carbonylation, Curtius rearrangement, and nucleophilic addition. This protocol provides a step‐economical and highly efficient reaction to access the wide range of valuable carbamates, symmetrical and unsymmetrical ureas with high yields under remarkable mild reaction conditions that are important factors in pharmaceutical science, biochemistry and agricultural industries. Furthermore, the magnetically recoverable nanocatalyst (Fe3 O4 @SiO2 /Pd(II)) can be conveniently and swiftly recycled using external magnet and reused at least for seven times without noticeable loss of its catalytic activity. Abstract : A palladium‐catalyzed domino method for the direct synthesis of carbamates and ureas has been developed by using readily available and economical starting materials (aryl halide, carbon monoxide, sodium azide, amines, and alcohols) in a one‐pot approach. This efficient and phosgene‐free process provided an inexpensive and attractive route to synthesize the products in good to excellent yields.